A PLEA FOR A BETTER BARGAIN: AN ANALYSIS OF PLEA BARGAINING IN INDIA - Kuttaiah, Bhairav (Commonwealth Law Review Journal, 2017)
The debate surrounding the introduction of plea bargaining in India1may only remain a moot point after 2006, but the implementation of the much-debated concept introduced as chapter XXI A2 , in the Code of Criminal Procedure, 1973 (hereinafter the ‘Code’) suggests that the legislature perhaps cannot see the wood for the trees. Historically, the Supreme Court of India has never expressed its support for the concept of plea bargaining3 and perhaps this is justifiable by the fact that introduction of plea bargaining has, unfortunately, not had the desired effect of reducing the number of cases pending before Courts in India. This paper aims to analyze some of the reasons that have hampered the utility of plea bargaining as a concept in India and makes suggestions regarding potential measures to make it more effective.